PERANCANGAN PERANGKAT LUNAK “SISTEM INFORMASI ABSENSI KARYAWAN” DI BAGIAN DOKUMEN CV. NIASA BANDUNG - Nova Indrayana Yusman (INTERNAL (Information System Journal), 2019)
CV Niasa is a company that engaged in the produce of foods namely chocolate and cakes. CV Niasa Provides chocolate and cakes with various types of shapes and flavors. However, the attendance system that the employee used is still very simple, in recording employee attendance. Is it very inefficient and ineffective because it spend a lot of time and the risk of error is relatively greater in recording of each employee’s absence. Therefore, it is necessary to create a system of employee attendance recording with the aim that the attendance recording activities will be more effective and efficient both in terms of time, and in terms of reducing the risk of error and can also facilitate the presentation of annual reports so that it can facilitate leaders to make decisions.             In the use of the program, the author chose to use Visual Basic programming 2010, because Visual Basic 2010 is the best and easiest to use in any programming language. Based on the background above, the author intends to make a computerized attendance system with the hope that employee attendance activities become more effective and efficient. In connection with this, the author compose this journal with the title : PERANCANGAN PERANGKAT LUNAK  “SISTEM ABSENSI KARYAWAN” Di BAGIAN DOKUMEN CV NIASA BANDUNG.CV Niasa is a company that engaged in the produce of foods namely chocolate and cakes. CV Niasa Provides chocolate and cakes with various types of shapes and flavors. However, the attendance system that the employee used is still very simple, in recording employee attendance. Is it very inefficient and ineffective because it spend a lot of time and the risk of error is relatively greater in recording of each employee’s absence. Therefore, it is necessary to create a system of employee attendance recording with the aim that the attendance recording activities will be more effective and efficient both in terms of time, and in terms of reducing the risk of error and can also facilitate the presentation of annual reports so that it can facilitate leaders to make decisions.                In the use of the program, the author chose to use Visual Basic programming 2010, because Visual Basic 2010 is the best and easiest to use in any programming language. Based on the background above, the author intends to make a computerized attendance system with the hope that employee attendance activities become more effective and efficient. In connection with this, the author compose this journal with the title : PERANCANGAN PERANGKAT LUNAK  “SISTEM ABSENSI KARYAWAN” Di BAGIAN DOKUMEN CV NIASA BANDUNG.